Digital Marketing Actions – Healthcare Providers of Dubai - Khan, Naseer; Khan, Bushra (Journal of Research in Marketing (ISSN: 2292-9355), 2020)
Digital Marketing has become important tool in campaigns, which attract and retain Internet users for healthcare issues. This study investigates the main ways in which patients can be gained and retained by the doctors / medical staff on behalf of healthcare providers of Dubai using digital marketing actions. This research study deals with a new approach that will optimize digital marketing tools and technologies for the evolution of patient trends, and therefore, will be of academic and professional use for doctors / medical staff, marketing managers and web solution developers working for the healthcare providers. The results and conclusions of the research identify the specific actions that must be carried out to attract and retain patients by healthcare providers that use the digital marketing tools and technology on the Internet. The results further indicate that the digital marketing of healthcare providers of Dubai through Internet is considered by the patients with the presence in social media has a reinforcing effect on building trust and long-term relationships by the doctors / medical staff.